PENGEMBANGAN MEDIA PEMBELAJARAN INSTALASI LISTRIK PORTABALE BERBASIS AUTOMATIC SMART CONTROL BUILDING PADA MATA KULIAH DASAR-DASAR INSTALASI LISTRIK DI PROGRAM STUDI S1 PENDIDIKAN TEKNIK ELEKTRO UNDIKSHA - Saputra, Gede Deva; Agus Adiarta; I Gede Made Surya Bumi Pracasitaram (Universitas Pendidikan Ganesha, 2023)
This study is used in order to be able to design and expand tools for activities teaching and learning in the form of an Automatic Smart-Based Portable Electrical Installation Trainer Control Building Portable in the Basics of Electrical Installation Course in the ProgramUndiksha Electrical Engineering Education Study Program. The type of this research is R&D (research and development). Presentation statistical analysis techniques used to process the data of content experts, media experts, and trials on students. On studysourced from questionnaires in taking data instruments content experts, media experts, and students. The results obtained were 93.1% of the results of the content expert validation test stated with very good results, a value of 97.3% was obtained from the media expert validation test with very good results, from 5 respondents as a group trial obtained very high qualifications, then obtained very high qualifications from trials large group of 15 respondents.